MISCONCEPTIONS ON REDOX REACTIONS USING THE FOUR TIER TEST - Rahmiati; Irawati, Ratna Kartika; Astutik, Trining Puji (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
The purpose of this research is to show the percentage of misconceptions experienced by students in class X MAN 3 Hulu Sungai Selatan by doing a four-tier test (four-level test) for each subconcept. The type of research used is descriptive statistics with a quantitative approach. The population of this study were students of class X MAN 3 Hulu Sungai Selatan with samples of class X MIA 1 and 2 totaling 63 people. The sampling technique used is purposive sampling. The data collection technique used a diagnostic test in the form of a four-tier test. The results showed that there was a misconception about the redox reaction material with an average of 33.45% which met the moderate criteria. Misconceptions of subconcepts Redox reactions are based on the gain and release of oxygen (16.67%), based on the gain and loss of electrons (39.68%), increase and decrease in oxidation number (38.10%), Oxidation number (12.70%), Oxidation-reduction reactions (44.44%), oxidizing agents and reducing agents (30.16%), and application of redox reactions (52.38%). The biggest misconception is in the sub-concept of applying redox reactions.